STRATEGI PEMASARAN PENDIDIKAN DALAM MENINGKATKAN MINAT ORANG TUA MEMILIH SEKOLAH STUDI KASUS SDIT RAUDHATUSSALAM MAHATO - Farida; Asrulla; Firdaus Jeka; Dwi Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze educational marketing strategies in increasing parents’ interest in choosing SDIT Raudhatussalam Mahato as an integrated Islamic elementary school. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and documentation. The research informants consist of the Foundation Supervisor, the principal, teachers, administrative staff, and parents selected purposively. Data analysis was conducted using the Miles, Huberman, and Saldana model, supported by source and method triangulation to ensure data validity.The findings indicate that SDIT Raudhatussalam Mahato implements a comprehensive educational marketing strategy by utilizing the educational services marketing mix (7P). Parents’ decisions are influenced by the quality of educational services, religious values, teacher competence, cost transparency, digital promotion, and interpersonal communication through word of mouth. The quality of educational services is proven to be the main pillar supporting the effectiveness of the school’s marketing strategy. Despite facing budgetary and resource constraints, the school is able to address these challenges through creative and collaborative strategies.